Agile Project Management for Sustainable Construction: A Systematic and Thematic Literature Review - Zamil, Ahmad M.; Alhusban, Mohammad (Salehan Institute of Higher Education, 2025)
This study aims to explore the implementation of Agile Project Management (APM) in Sustainable Construction Projects (SCPs) to identify thematic trends, challenges, and enablers shaping agile adoption in the construction industry. The objective of this review is to determine how agile principles improve collaboration, adaptability, and sustainability outcomes. A systematic review of 104 scholarly articles published between 2006 and 2025 was performed using the PRISMA protocol to ensure rigour and transparency. Thematic analysis was conducted with NVivo and ATLAS.ti to code, visualise, and validate evolving patterns across the literature. The analysis revealed five major themes: iterative planning, responsiveness to change, stakeholder collaboration, digital facilitation, and sustainability integration. These results reveal that agile principles significantly contribute to sustainable construction by improving adaptability, decision-making, and communication processes, in spite of barriers such as organisational resistance and policy constraints. The integrative use of NVivo and ATLAS.ti improved depth and methodological reliability through cross-validation of themes. The novelty of this review lies in its dual-software thematic framework and its demonstration of how agile practices can transform sustainability-orientated construction management. It provides methodological and practical insights for researchers and practitioners aiming to embed agility in sustainable development goals.